THE IMPACT OF NAFTA IN MEXICO - Hesti Eka Denata; Novera Luthfiani; Fatimatuz Zahro (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
This research paper aims to analyze the impact of regionalism and the North American Free Trade Agreement (NAFTA) trading system on the Mexican economy. This analysis uses Mexican economic data from before and after the implementation of NAFTA to analyze its impact on the Mexican economy. Mexico experienced good economic growth after the implementation of NAFTA. Although the impact was not evenly distributed across all economic sectors, the manufacturing and export sectors experienced good growth as NAFTA provided easier access to the US market. The positive impact of the implementation of NAFTA on the Mexican economy was an increase in the flow of foreign investment into Mexico. This agreement opened the door for foreign companies to invest and help in the development of certain sectors such as manufacturing and automotive in Mexico. However, Mexico also faces challenges with the NAFTA agreement. One of them is vulnerability to international market instability and the United States' changing trade policies. In addition, some sectors of the Mexican economy still face systematic barriers and inequities in the distribution of economic benefits.